Percepção de trabalhadores sobre conflitos interpessoais com idosos institucionalizados - Gewehr, Melissa (2019)
The institutionalization of the elderly portrays a reality triggered by epidemiological, demographic, health and social issues. The presence of institutional routines delineate the occurrence and intensity of conflicts. Such problematic is part of the daily care of professionals who work in this place. This study has the main aim: analyze the perception of workers of a long-term care institution for the elderly about the occurrence of interpersonal conflicts with institutionalized elderly. And as specific objectives: describe the situations of interpersonal conflict in the daily life of institutionalized elderly and describe how workers deal with the interpersonal conflict situations of institutionalized elderly. This is a exploratory, descriptive and qualitative research conducted in a long-term care institution for the elderly located in the central region of the state of Rio Grande do Sul. Data were collected through semi-structured interviews whoose data were analysed with the thematic content analysis of Minayo operative proposal. The research was approved with Certificate of Presentation for Ethical Appreciation 67059417.5.0000.5346. ILPI has operating standards and includes services, including laundry that takes care of sanitizing, conserving, maintaining and controlling the institution's trousseau and the clothes of the elderly. The data demonstrated a naturalization, by the workers, of the process of “mortification of the self” suffered by the elderly and triggered by institutionalization. Conflict situations emerge due to the resistance of the elderly to this process: against the loss of identity, autonomy, privacy, individuality and freedom. In these attempts at resistance, disputes arise over spaces of identity and affronts to masculinity. The workers perceive these attempts as manifestations of dissatisfaction of the elderly with the service of professionals, with the food offered and in other areas of the institution. Other situations of conflict occur when the elderly behave in an altered manner due to the presence of dementia symptoms and their attitudes are contradicted by others. To deal with various conflicts, workers use argumentation and persuasion as approaches to dialogue. The purposes of dialogue vary from warnings, conciliations, and negotiations. Faced with the lack of these strategic resources, they employ coercion. Faced with the existence of recurring conflicts with physical violence, even involving threats to life, professionals use distances to drive them away and withdraw of sharp objects.. It is concluded that the trivialization of the “mortification of the self” inflicted on the elderly by current norms - such as “the laundry of identities” - makes it impossible a final settlement of conflicts by workers' strategies: perpetuating the occurrence of conflicts.